Revizorjevo poročilo po novem in prenovljenih Mednarodnih standardih revidiranja - Zdolšek, Daniel (Podjetje in delo, 2019)
International Standards on Auditing are used to prepare an auditor's report that includes an opinion on the financial statements (single or consolidated) of the audited entity. In May 2018, the Slovene translation of new and revised International Standards on Auditing (new with number 701 and revised with numbers 700, 705, 706, 570 and 720) were publicly released. These Standards have to be used in the audits of financial statements. New and revised International Standards on Auditing were prepared as a response of the audit profession to the global financial and economic crisis started in 2008. The aim is/was to increase the confidence of financial statements' users in the financial statements and financial statements' audits, increase transparency and information value of auditor's report, increase communication between an auditor and various stakeholders, etc. This paper presents the form of the auditor's report and its (more important) content/sections, including some provided illustrations prepared in accordance with the new and revised International Standards on Auditing. An auditor's report (with auditor's unmodified opinion on the financial statements of the audited entity) which is and will be most frequently used in actual practice is illustrated.
Keywords: podjetja; računovodski standardi; računovodsko poročanje; revizija